The print and the process : taking compelling photographs from vision to expression - DuChemin, David (Voices that matter., 2013)
"David duChemin presents four monographs, with a series of 30 prints from each project: Venice, Iceland, Kenya, and Antarctica. After each set of photographs, duChemin takes the reader behind the scenes to discuss the motivation behind the project, and in turn discusses each image with regard to how it was conceived, composed, or post-processed ... both behind the camera and in the digital darkroom"--